Psycho physical test in normal individual and diabetic patients with and without diabetic retinopathy: comparative study - Sapna Raghuwanshi; Rashmi Kumar; Shivkumar Raghuwanshi (International Journal of Medical Research and Review, 2018)
Purpose: To investigate the differentiating ability of psychophysical test which include contrast sensitivity function (CSF), dark adaptation (DA)and best corrected visual acuity (BCVA) in detecting functional losses in diabetic participants with and without retinopathy.Methods: In this cross-sectional study we examined 90 patients in L.N. Medical college and J. K Hospital, Kolar road, Bhopal between June to November 2017 including 60 diabetic patients (30 with retinopathy and 30 without retinopathy in fundus photography) with 30 control non-diabetic subjects matched for age and sex. The diabetic participants were sub grouped according to the level of retinopathy (EDTRS classification). CSF was examined by means of pelli robson chart in each eye; DA was assessed with photostress test and BCVA by Snellen chart.Results: When comparing visual performance of the right and left eyes of patients in each group, CSF was significantly lower in the diabetic eyes with retinopathy than in the normal eyes or the diabetic eyes without retinopathy. Comparing to control group, there was a statistically significant CSF loss in the diabetic eyes without retinopathy (P<0.05). The mean logMAR BCVA and DA abnormalities were significantly higher in the diabetic eyes with retinopathy than in the normal eyes or the diabetic eyes without retinopathy (P<0.001). There was no significant difference observed in mean log MAR BCVA and DA between those of diabetic eye without retinopathy compared to the control group.Conclusion: There was significant difference observed in visual performance of those diabetics with retinopathy compared to those without. The findings also suggest that the appropriate combination of existing tests can be a useful method of improving screening accuracy in diabetic patients.